2020
DOI: 10.1007/s12198-020-00220-4
|View full text |Cite
|
Sign up to set email alerts
|

REAL ID: privacy concerns still a factor, but weakly so

Abstract: Statewide research conducted to design a campaign to inform Montana residents about the REAL ID Act supported previous claims that some Rocky Mountain residents view the law as an invasion of privacy. Although most Montana residents (60%, n = 194) planned to get their REAL IDs within the first year that it became available, 43% ( n = 141) of respondents to a survey of registered voters ( n = 325) intended to wait more than one year or never o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…For instance, in the United Kingdom, Maio et al found a backlash reaction to antiracism messages when people were ambivalent toward ethnic minority groups [ 6 ]. Keller et al found backlash reactions occurred among men when presented with domestic violence-prevention messages that stereotyped men as perpetrators [ 7 ]. Similar backlash reactions have occurred in response to anti-littering messages in the United States [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in the United Kingdom, Maio et al found a backlash reaction to antiracism messages when people were ambivalent toward ethnic minority groups [ 6 ]. Keller et al found backlash reactions occurred among men when presented with domestic violence-prevention messages that stereotyped men as perpetrators [ 7 ]. Similar backlash reactions have occurred in response to anti-littering messages in the United States [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although inoculation messages to promote public security measures in the wake of 9/11 or COVID-19 may have been sensible, erosion of public opposition to the Real ID Act seems to have undermined the need for such sophisticated marketing campaigns in this instance. No good data is available to document the level of public resistance to the Act at the time of its passage (Keller et al 2020). The fact that numerous state governments opposed the federal mandate with anti-Real ID statutes over the past 10-15 years, does not confirm the presence of popular opposition -either then or now.…”
Section: The Real Me Campaignmentioning
confidence: 99%